2016
DOI: 10.1038/srep35502
|View full text |Cite
|
Sign up to set email alerts
|

Layered double hydroxide-oxidized carbon nanotube hybrids as highly efficient flame retardant nanofillers for polypropylene

Abstract: Aqueous miscible organic layered double hydroxides (AMO-LDHs) can act as organophilic inorganic flame retardant nanofillers for unmodified non-polar polymers. In this contribution, AMO [Mg3Al(OH)8](CO3)0.5·yH2O LDH–oxidized carbon nanotube (AMO-LDH–OCNT) hybrids are shown to perform better than the equivalent pure AMO-LDH. A synergistic effect between the AMO-LDH and OCNT was observed; this endows the hybrid material with enhanced flame retardancy, thermal stability, and mechanical properties. The thermal stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 34 publications
4
48
1
1
Order By: Relevance
“…In spite of considerable researches related to pristine LDH‐INEs have been made and showed a trend of rapid growth, inferior electrical conductivity and limited active sites resulted restricted electrocatalytic performance still hinder the widely application of pristine LDH‐INEs . To further improve the electrochemical performance of pristine LDH‐INEs and expand the application areas, the fabrication of more sophisticated materials both in dimension, composition, and structure is badly needed.…”
Section: Ldh‐inesmentioning
confidence: 99%
“…In spite of considerable researches related to pristine LDH‐INEs have been made and showed a trend of rapid growth, inferior electrical conductivity and limited active sites resulted restricted electrocatalytic performance still hinder the widely application of pristine LDH‐INEs . To further improve the electrochemical performance of pristine LDH‐INEs and expand the application areas, the fabrication of more sophisticated materials both in dimension, composition, and structure is badly needed.…”
Section: Ldh‐inesmentioning
confidence: 99%
“…36,37 This simple technique uses organic solvents to wash LDH particles immediately after synthesis and can tune the surface of LDHs to be hydrophobic, enabling them to be effectively dispersed in apolar environments. [38][39][40] AMOST modified LDHs have also been found to disperse better in hydrophobic polymers than unmodified LDH particles.…”
Section: They Can Be Described By the General Chemical Formulamentioning
confidence: 99%
“…Ibuprofen intercalated MgAl-LDH was synthesized using a hydrothermal method. 40,41 A metal precursor solution containing 2.032 g MgCl 2 Á6H 2 O and 1.207 g AlCl 3 Á9H 2 O (Mg : Al = 2 : 1) in 20 mL deionized water was added drop-wise into a second solution comprising 2.1 g of sodium ibuprofen dissolved in 20 mL of H 2 O. The pH was kept constant at ca.…”
Section: Synthesis Of Drug Intercalated Ldhmentioning
confidence: 99%
“…However, it is found that most of the relevant literature investigated the gas release of PVC based on the cone results or thermogravimetric analysis (TGA)–Fourier transform infrared (FTIR). Generally, the layered catalyst increases the specific surface area and the contact area with the material, which can enhance the catalytic effect, and a catalyst with a layered structure has a better catalytic effect than a catalyst with the particulate structure.…”
Section: Introductionmentioning
confidence: 99%